How do you simplify 2a - 5(a +1)?

4 Answers
Mar 4, 2018

First... expand the brackets

While expanding... you multiply all the terms with the term to be multiplied to

2a-5(a+1)=2a-5a-5
Solve
-3a-5

If you'll take 0
-3a-5=0
-3a=5
a=-5/3

Mar 4, 2018

By Distributing; the answer is -3a-5

Explanation:

Distribute the 5 into the parenthesis:

2a-5a-5

Simplify:

-3a-5

Mar 4, 2018

=-3a-5

Explanation:

2a-5(a+1)

= 2a-5×a-5×1

= 2a-5a-5

Thus,

= -3a-5

Mar 4, 2018

=-3a-5

Explanation:

2a-5(a+1)

Distribute

=2a+(-5)(a)+(-5)(1)

2a - 5a - 5

=-3a - 5